Venous Thromboembolism Secondary to Adult-Onset Still’s Disease: a Case Report - Calborean Veronica; Gheorman Victor; Constantin Cristian; Istrătoaie Octavian (Journal of Cardiovascular Emergencies, 2018)
A 56-year-old man presented to the emergency department with pain, swelling, and restricted mobility of the left lower limb and shortness of breath on exertion in the previous 3 days. Seven months prior to this presentation, he had been diagnosed with adult-onset Still’s disease based on the Yamuguchi criteria, after excluding the presence of any other disease. The patient had been treated with prednisolone and methotrexate. Subsequent investigations revealed that he developed bilateral deep venous thrombosis and bilateral pulmonary emboli. This case emphasizes that adult-onset Still’s disease can be a rare but life-threatening cause of venous thromboembolism.